Influence of Moisture In Step-voltage Measurements of PVDF - Faria, R. M.; Nogueira, J. S.; Alves, N. [UNESP] (IOP Publishing, 1992)
Step-voltage current measurements carried out with commercial poly(vinylidene fluoride) (PVDF) under vacuum showed a prominent peak in the charging current when a sample had previously been in contact with a humid environment. This effect tends to disappear in subsequent measurements performed under the same experimental conditions, giving evidence that it is connected with extrinsic carriers which are swept out of the sample by the external electric field. A model based on a field-dependent ionic dissociation of water molecules absorbed by the bulk of the sample was developed to explain the phenomenon. © 1992 IOP Publishing Ltd.